Dysarthria and quality of life in neurologically healthy elderly and patients with Parkinson's disease - Lirani-Silva, Camila; Mourão, Lúcia Figueiredo; Gobbi, Lilian Teresa Bucken [UNESP] (Sociedade Brasileira de Fonoaudiologia, 2015)
PURPOSE: To compare the speech and voice of Parkinson's disease (PD) patients and neurologically healthy elderly adults (control group, CG), to find out whether these features are related to the disease or the normal aging process, and investigate the impact that dysarthria has on the Quality of Life (QoL) of these individuals. METHODS: This is a cross-sectional study involving 25 individuals, 13 patients with PD and 12 CG. All the participants underwent vocal assessment, perceptual and acoustic analysis, based on Dysarthria Assessment Protocol and analysis of QoL using a questionnaire, Living with Dysarthria. The data underwent statistical analysis to compare the groups in each parameter. RESULTS: In the assessment of dysarthria, patients with PD showed differences in prosody parameter (p=0.012), at the habitual frequency for females (p=0.025) and males (p=0.028), and the extent of intensity (p=0.039) when compared to CG. In QoL questionnaire, it was observed that patients with PD showed more negative impact on the QoL compared to CG, as indicated by the total score (p=0.005) with various aspects influencing this result. CONCLUSION: The degree of modification of speech and voice of patients with PD resembles those seen in normal aging process, with the exception of prosody and the habitual frequency, which are related to the greatest negative impact on the QoL of patients with PD.

OBJETIVO: Comparar a fonoarticulação de um grupo com doença de Parkinson (DP) e um Grupo Controle (GC) de sujeitos neurologicamente sadios, a fim de descobrir se essas características são relacionadas à doença ou ao processo normal de envelhecimento, e investigar o impacto que a disartria acarreta à Qualidade de Vida (QV) desses sujeitos. MÉTODO: Trata-se de um estudo transversal com a participação de 25 sujeitos, sendo 13 pacientes com DP e 12 GC. Todos os participantes foram avaliados quanto à disartria, análise perceptivo-auditiva e acústica, com base no Protocolo de Avaliação da Disartria, e à QV, utilizando-se o questionário Vivendo com Disartria. Os dados foram comparados entre os grupos em cada parâmetro. RESULTADOS: Na avaliação da disartria, o grupo com DP apresentou diferenças no parâmetro prosódia (p=0,012), na frequência habitual para os gêneros feminino (p=0,025) e masculino (p=0,028), e na média da extensão de intensidade (p=0,039), quando comparado ao GC. Em relação à QV, observou-se que a disartria apresenta um impacto mais negativo na QV dos pacientes com DP, quando comparados aos sujeitos do GC, conforme observado no escore total (p=0,005) e nos aspectos que influenciaram esse resultado. CONCLUSÕES: O grau de modificação da fonoarticulação dos pacientes com DP assemelha-se aos presentes no processo normal de envelhecimento, com exceção da prosódia e da frequência habitual, que estão relacionadas com o impacto mais negativo na QV dos sujeitos com DP.
Disartria e qualidade de vida em idosos neurologicamente sadios e pacientes com doença de Parkinson
Keywords: Parkinson's disease; Aging; Dysarthria; Voice; Quality of Life; Doença de Parkinson; Envelhecimento; Disartria; Voz; Qualidade de vida